Carbon nano-tubes in improving the mechanical property of cement-based composite materials (Fracture and Structural Integrity, 2017)
Carbon nano-tubes as a kind of novel nanometer material have been extensively applied in cement-based composite materials to improve their properties. This study prepared carbon nano-tubes cement based composite materials by evenly scattering carbon nano-tubes in cement materials using ultrasonic method and emphatically investigation the improvement of the mechanical property. The results demonstrated that, the addition of carbon nano-tubes could significantly relieve the mechanical properties of cement based composite materials. When the mixing amount of carbon nano-tubes reached the optimal value, i.e., 0.1%, the improvement of the mechanical property of the carbon nano-tubes cement based composite materials was the best. The microstructure analysis using scanning electron microscope suggested that, carbon nano-tubes produced bridging and pullout effects in the cement-based materials, which enhanced the damage resistance of the cement based materials.
Keywords: Carbon nano-tubes; Cement-based composite material; Mechanical property